The National Emergency Access Target (NEAT) and the 4‐hour rule: time to review the target. Issue 9 (16th May 2016) - Sullivan, Clair; Staib, Andrew; Khanna, Sankalp; Good, Norm M; Boyle, Justin; Cattell, Rohan; Heiniger, Liam; Griffin, Bronwyn R; Bell, Anthony Jr; Lind, James; Scott, Ian A
Abstract: Objective: We explored the relationship between the National Emergency Access Target (NEAT) compliance rate, defined as the proportion of patients admitted or discharged from emergency departments (EDs) within 4 hours of presentation, and the risk‐adjusted in‐hospital mortality of patients admitted to hospital acutely from EDs. Design, setting and participants: Retrospective observational study of all de‐identified episodes of care involving patients who presented acutely to the EDs of 59 Australian hospitals between 1 July 2010 and 30 June 2014. Main outcome measure: The relationship between the risk‐adjusted mortality of inpatients admitted acutely from EDs (the emergency hospital standardised mortality ratio [eHSMR]: the ratio of the numbers of observed to expected deaths) and NEAT compliance rates for all presenting patients (total NEAT) and admitted patients (admitted NEAT). Results: ED and inpatient data were aggregated for 12.5 million ED episodes of care and 11.6 million inpatient episodes of care. A highly significant ( P < 0.001) linear, inverse relationship between eHSMR and each of total and admitted NEAT compliance rates was found; eHSMR declined to a nadir of 73 as total and admitted NEAT compliance rates rose to about 83% and 65% respectively. Sensitivity analyses found no confounding by the inclusion of palliative care and/or short‐stay patients. Conclusion: As NEAT compliance rates increased, in‐hospital mortality of emergency admissions declined, although this direct inverse relationship is lost once total and admitted NEAT compliance rates exceed certain levels. This inverse association between NEAT compliance rates and in‐hospital mortality should be considered when formulating targets for access to emergency care.